Infestation levels of Zaprionus indianus (Diptera: Drosophilidae) in different host fruits - Vieira, Júlia Gabriela Aleixo; Wollmann, Jutiane; Schlesener, Daniele Cristine Hoffmann; Mendes, Sávio Ritta; Garcia, Flávio Roberto Mello (Revista de Ciências Agroveterinárias, 2019)
The fig fly, Zaprionus indianus Gupta, 1970 (Diptera: Drosophilidae) is a generalist species, but economically important in the fig culture, in which it is considered a primary pest. This study aimed to verify the levels of natural infestation of Z. indianus in blackberry, strawberry guava, Physalis, guava, blueberry, strawberry and Surinam cherry fruits in southern Brazil. The indexes were calculated through the number of flies emerged per fruit and the number of flies per mass (Kg) of fruit. The highest rates of infestation (fly/Kg) were observed in blackberries (1295), strawberry guavas (1253) and Surinam cherries (1016); for the second index, (M/n) in guavas (26.17), strawberry guavas (11.87) and strawberries (10.27). Fruits collected directly from the plant were more infested compared with fruits collected from the soil, which may be due to the initial attack of Drosophila suzukii (Matsumura, 1931) (Diptera: Drosophilidae) and Anastrepha spp., pests already disseminated in the region.